(untitled) (Czech Journal of International Relations, 2024)
Czechoslovak-Polish Negotiations of the Establishment of Confederation and Alliance 1939-1944. Czechoslovak Diplomatic Documents. Editors Ivan Št’ovíček and Jaroslav Valenta. Publishing House Karolinum and the Istitute of History, Academy of Sciences of the Czech Republik, Prague 1995, 449 stran, ISBN 80-7184-123-4.